Dislocation Network‐Boosted PtNi Nanocatalysts Welded on Nickel Foam for Efficient and Durable Hydrogen Evolution at Ultrahigh Current Densities. Issue 1 (7th November 2022) - Zhou, Miao; Cheng, Chuanqi; Dong, Cunku; Xiao, Liyang; Zhao, Yao; Liu, Zhanwei; Zhao, Xueru; Sasaki, Kotaro; Cheng, Hao; Du, Xiwen; Yang, Jing
Abstract: Large‐scale application of alkaline water electrolysis for high‐rate hydrogen production is severely hindered by high electricity cost, mainly due to difficulties to acquire cost‐effective catalytic electrodes with both extremely low overpotential and long‐term durability at ultrahigh current densities (≥1 A cm −2 ). Here it is demonstrated that by adopting a synthetic method of laser direct writing in liquid nitrogen via a commercial laser welding machine, a remarkably efficient and durable electrode with large area and low platinum content is obtained, where PtNi nanocatalysts with dislocation network are firmly welded on a nickel foam (NF). The dense dislocation network not only improves intrinsic activity of a majority of surface‐active sites induced by coupled compressive‐tensile strains synergistically promoting both Volmer and Tafel steps of alkaline hydrogen evolution reaction (HER), but also well stabilizes surface dislocations for HER at ultrahigh current densities. Such a robust electrode achieves record‐low overpotentials of 5 and 63 mV at 10 and 1000 mA cm −2 in alkaline medium, respectively, exhibiting negligible activity decay after 300 h chronoamperometric test at 1 A cm −2 . It displays a high Pt mass activity 16 times higher than 20 wt% Pt/C loaded on NF, surpassing most of the recently reported efficient Pt‐based catalysts. Abstract : A robust low‐platinum electrode over a large area is prepared. PtNi nanocatalysts with dense dislocation network are firmly welded on a nickel foam, not only dramatically enhancing alkaline hydrogen evolution reaction intrinsic activity due to coupled compressive‐tensile strains but also owning abundant active sites and superior stability, beneficial for efficient and durable hydrogen production at ultrahigh current densities.